A crowdsourcing approach to collecting photo-based insect and plant observation records - Osawa, Takeshi (Biodivers Data J, 2017)
Abstract. BACKGROUND: Scientific field observation by members of the public is known as citizen science and has become popular all across the world. Citizen science is advantageous for collecting large amounts of scientific data and can be seen as a crowdsourcing approach to data collection. Information and communications technology is enhancing the availability of citizen science. Mobile devices, such as mobile phones, that have a digital camera with a global positioning system (GPS) are necessities for contemporary life and can be utilised as powerful observation tools in citizen science. NEW INFORMATION: A web-based system has been developed as a data collection tool for citizen science. Participants submit an e-mail with a photo taken by their mobile phones. The photos contain location information, which can be easily and automatically embedded if the mobile phone is equipped with GPS. Collaboration has been undertaken with regional event managers, such as museum curators and held citizen science events in each region and for various target taxonomic groups. All photos were stored in the data server and the organisms were taxonomically identified by citizen scientists, regional managers and the authors. In total, 154 species and 843 data records were collected in this project conducted from 2011 to 2016.